2017
DOI: 10.1002/ss.20242
|View full text |Cite
|
Sign up to set email alerts
|

Race, Religion, and Spirituality for Asian American Students

Abstract: This chapter describes how race, ethnicity, religion, and spirituality uniquely interact for Asian American college students, including a discussion of the diverse religious and spiritual backgrounds of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the present study, the divisiveness identified by evangelical Christian Asian American students may be reflective of the worldview experiences of their AAPI family and friends across campus. Our findings affirm that students’ intersecting identities are essential considerations when creating practice-based improvements to campus climate (see Park, 2018; Park and Dizon, 2017).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the present study, the divisiveness identified by evangelical Christian Asian American students may be reflective of the worldview experiences of their AAPI family and friends across campus. Our findings affirm that students’ intersecting identities are essential considerations when creating practice-based improvements to campus climate (see Park, 2018; Park and Dizon, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Evangelical students who identified as Asian, Asian American, or Pacific Islander perceived more divisiveness than the average evangelical student. As many as 40% of Asian Americans identify as Christian, marking it the largest religious identity among Asian Americans (Park and Dizon, 2017). However, both identification within the Christian moniker (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic socialization and religious upbringing are an intertwined experience for religious Asian Americans (Park & Dizon, 2017). Furthermore, relationship to God can mirror relationship to self and others (Kirkpatrick & Shaver, 1990).…”
Section: God Representations and Mental Healthmentioning
confidence: 99%
“…Indeed, it is uncommon, even in higher education, for students to be exposed to religious literacy education. It comes as no surprise, then, that students with minoritized ethno‐religious identities often report being misunderstood by their professors (Park & Dizon, 2017), which can happen when students observe incongruence between what they see presented in the curriculum and what their lived experiences are. While there is certainly a growing call to help students develop religious literacy, there is also a disturbing trend of institutions choosing to eliminate religious studies departments altogether (Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%